2016
DOI: 10.4103/0366-6999.185871
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Multiple Risk Assessment Tools to Predict Mortality for Adult Respiratory Distress Syndrome with Extracorporeal Membrane Oxygenation Therapy

Abstract: Background:There has been no external validation of survival prediction models for severe adult respiratory distress syndrome (ARDS) with extracorporeal membrane oxygenation (ECMO) therapy in China. The aim of study was to compare the performance of multiple models recently developed for patients with ARDS undergoing ECMO based on Chinese single-center data.Methods:A retrospective case study was performed, including twenty-three severe ARDS patients who received ECMO from January 2009 to July 2015. The PRESERV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…The hallmarks of ARDS are membrane permeability alteration, surfactant dysfunction, diffuse interstitial and alveolar edema, the formation of a transparent membrane, and alveolar collapse. Previous studies have shown that multiple organ dysfunction syndrome (MODS), acute physiology and chronic health evaluation score II (APACHE II score) [2], and shock [3] are related to the ARDS prognosis. Inflammatory dysfunction and cell apoptosis are involved in ARDS development.…”
Section: Introductionmentioning
confidence: 99%
“…The hallmarks of ARDS are membrane permeability alteration, surfactant dysfunction, diffuse interstitial and alveolar edema, the formation of a transparent membrane, and alveolar collapse. Previous studies have shown that multiple organ dysfunction syndrome (MODS), acute physiology and chronic health evaluation score II (APACHE II score) [2], and shock [3] are related to the ARDS prognosis. Inflammatory dysfunction and cell apoptosis are involved in ARDS development.…”
Section: Introductionmentioning
confidence: 99%
“…(8-15) That is, higher APACHE II scores were associated with greater hospital mortality in the examined groups of subjects.…”
mentioning
confidence: 96%
“…[789] Although the number of hospitals that have performed VV-ECMO for ARF rescue is increasing rapidly, the quantity in each center is limited, and no unified registration network exists in our country. This situation hinders the standardization and management of ECMO and leads to poor outcomes.…”
Section: Evolution Of Extracorporeal Membrane Oxygenation For Acute Rmentioning
confidence: 99%